Initial high-efficacy disease-modifying therapy in multiple sclerosis: A nationwide cohort study. (25th August 2020) - Buron, Mathias Due; Chalmer, Thor Ameri; Sellebjerg, Finn; Barzinji, Ismael; Christensen, Jeppe Romme; Christensen, Mette Kirstine; Hansen, Victoria; Illes, Zsolt; Jensen, Henrik Boye; Kant, Matthias; Papp, Viktoria; Petersen, Thor; et al.
Abstract : Objective: To determine the effectiveness of high-efficacy disease-modifying therapies (heDMTs) vs medium-efficacy disease-modifying therapies (meDMT) as the first treatment choice in treatment-naive patients with multiple sclerosis (MS) on disability worsening and relapses. We assessed this using a nationwide population-based MS registry. Methods: We identified all patients starting a heDMT as first-time treatment from the Danish Multiple Sclerosis Registry and compared treatment outcomes with a propensity score matched sample of patients starting meDMT. Results: We included 388 patients in the study: 194 starting initial therapy with heDMT matched to 194 patients starting meDMT. At 4 years of follow-up, the probabilities of a 6-month confirmed Expanded Disability Status Scale (EDSS) score worsening were 16.7% (95% confidence interval [CI] 10.4%–23.0%) and 30.1% (95% CI 23.1%–37.1%) for heDMT and meDMT initiators, respectively (hazard ratio [HR] 0.53, 95% CI 0.33–0.83, p = 0.006). Patients initiating heDMT also had a lower probability of a first relapse (HR 0.50, 95% CI 0.37–0.67). Results were similar after pairwise censoring and in subgroups with high baseline activity, diagnosis after 2006, or information on baseline T2 lesion load. Conclusion: We found a lower probability of 6-month confirmed EDSS score worsening and lower probability of a first relapse in patients starting a heDMT as first therapy, compared to a matched sample starting meDMT. Classification of evidence: This study provides Class III evidence that for patients with MS, starting heDMT lowers the risk of EDSS worsening and relapses compared to starting meDMT.